Hypohidrotic ectodermal dysplasia: A unique approach to esthetic and prosthetic management: A case report - Shigli A; Reddy RP; Hugar S; Deshpande D (Wolters Kluwer Medknow Publications, 2005)
Hypohidrotic ectodermal dysplasia is a rare congenital disease that affects several ectodermal structures. The condition is usually transmitted as an x-linked recessive trait, in which gene is carried by the females and manifested in males. Manifestations of the disease differ in severity and involve teeth, skin, hair, nails and sweat and sebaceous gland. Ectodermal dysplasia is usually a difficult condition to manage. Prosthodontically, because of the typical oral deficiencies, and afflicted individuals are quite young to receive extensive prosthodontic treatment, which restores their appearance and helps them, for the development of positive self-image. This case report describes the management of upper jaw with over denture with copings on existing teeth i.e. two permanent peg shaped centrals as well as lateral incisors. However with adequate of retainer lower denture was provided with a new treatment modality.